أثر المعاملة بحمض الساليسيك (Salicylic acid) في نمو وإنتاجية الخيار الحقلي Cucumis sativus L. - حويجي, مها (Latakia University Journal -Biological Sciences Series, 2019)
The study was conducted during 2014-2015 growing seasons in Maschketa village-Latakia To investigate the effect of different application methods of Salicylic acid on growth and yield of cucumber plants (variety Apollo-Magic F1), four concentrations of Salicylic acid (0.5 – 1 – 1.5 – 2 mM) were applied in two different treatments, irrigation and spraying of young Cucumber plants with studied concentration. The experiment was split block design with three replications. plants, and the positive effect was differ according to the treatment methods and the concentrations of Salicylic acid. However, the treatments of spray with salicylic acid showed better results compared with irrigated and non treated plants. Also, The the two concentrations (1 and 1.5 mM) respectively give significantly better results comparing with (0.5 and 2 mM) concentration in most studied characters. The (Sp1) treatment gave the best results in terms of plant growth(263.94cm), number and percentage of female flowers (31.11), (73.09%) respectively, and significantly the average number of fruit on plant (30.02) as well as plant productivity (2.411kg). أجري البحث خلال عامي 2014-2015 في قرية مشقيتا التابعة لمحافظة اللاذقية بهدف تحديد أثر المعاملة بحمض الساليسيك على نمو وإنتاجية نبات الخيار الحقلي. استخدم في التجربة أربع تراكيز من حمض الساليسيك (0.5 , 1, 1.5, 2 ميلليمول) حيث تمت معاملة النباتات الفتية لصنف الخيار أبولو (Apollo Magic F1) إما بطريقة الري أو بالرش الورقي بالتراكيز السابقة. أظهرت النتائج الأثر الإيجابي لحمض الساليسيك في نمو وإنتاج نبات الخيار وقد تباينت النتائج وفقاً للتركيز المستخدم ولطريقة المعاملة, بالإجمال أعطت معاملات الرش بحمض الساليسيك نتائج أفضل من معاملات السقاية والشاهد, أما فيما يتعلق بالتراكيز المختبرة فقد تفوقت معاملات التراكيز المتوسطة 1 و 1.5 ميلليمول على معاملات التركيز المنخفض 0.5 التركيز المرتفع 2 ميلليمول إضافة للشاهد في أغلب الصفات المدروسة. أعطت المعاملة Sp1 أفضل النتائج من حيث متوسط طول النبات (263.94سم), وعدد الأزهار المؤنثة (31.11) ونسبتها المئوية (73.09%), وبشكل ملحوظ متوسط عدد الثمار على النبات (30.02) وإنتاجية النبات (2.411 كغ).